Scottish and English architecture: a “provincial” relationship? - Clarisse GODARD DESMAREST (E-REA)
This article seeks to explore the specificities of Scottish architecture in relation to English architecture. It focusses first on the orthodoxies presented within past literature, and how these have been sometimes unhelpful to scholars wishing to address this question. The article then seeks to identify, and then to analyse, what clearly is a national style of architecture which can be characterised, in summary, as castellated. The discussion that follows on Revivalism(s) is articulated relative to long-standing issues of nationhood; considering Scotland first as an independent European state, over many centuries until union with England in 1707; and secondly, thereafter, Scotland’s attempt to define its status within both the British union and the empire; an arrangement in which the paradigms were those of England; but an England which tolerated a degree of cultural individuality so long as political adherence to the “core” was assured. The article builds upon recent research in social and political history, as well as architecture and visual culture, and demonstrates that Scotland’s interest in its own past heritage, and its clear individuality (or “different-ness”) in architectural style, is closely connected to the nation’s recurring attempts to find a voice in a larger political entity.